Controlling Product Distribution of CO2 Reduction on CuO‐Based Gas Diffusion Electrodes by Manipulating Back Pressure. Issue 12 (21st October 2022) - Sahin, Baran; Leung, Jane J.; Magori, Erhard; Laumen, Steffen; Tawil, Angelika; Simon, Elfriede; Hinrichsen, Olaf
Abstract : The electrochemical reduction reaction of CO2 (CO2 RR) is a promising avenue toward the renewable energy‐driven transformation of a greenhouse gas toward fuels and value‐added chemicals. While copper uniquely can catalyze this reaction to longer carbon chains, Cu‐based electrodes continue to face numerous challenges, including low selectivity toward desired products and poor stability. To unlock its potential for large‐scale industrial implementation, great interest is shown in tackling these challenges, primarily focusing on catalyst and electrode modifications and thereby leaving a research gap in the effects of operation conditions. Herein, back pressure application is introduced in CO2 electrolyzers at industrially relevant current densities (200 mA cm −2 ) in order to steer selectivity toward C2+ products. The back pressure adjusts CO2 availability at the electrode surface, with a high CO2 surface coverage achieved at Δ P = 130 mbar suppressing the competing hydrogen evolving reaction for 72 h and doubling of stable ethylene production duration. Faradaic efficiency of 60% for C2+ products and overall C2+ conversion efficiency of 19.8% are achieved with the easily implementable back pressure operation mode presented in this study. It is proven to be a promising tool for product selectivity control in future upscaled Cu‐based CO2 electrolysis cells. Abstract : Back pressure enables control over product selectivity toward C2+ products, up to a Faradaic selectivity of 60%. It enhances the stability of the CO2 RR significantly, from 36 to 72 h of stable ethylene production. Its easy implementability renders it a promising tool to be used in commercialized CO2 RR cells in the future.